Hubungan Kadar Bahan Organik Tanah dengan Keanekaragaman Makrofaun Tanah pada Lahan Pertanian di Kecamatan Baturiti - STEFANIA DESYANI DERGONG; A.A. ISTRI KESUMADEWI; I WAYAN DANA ATMAJA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
The Relationship between Soil Organic Matter Levels with Diversity of Soil Macrofauna on Agricultural Land in Baturiti District This study aims to determine the level of soil macrofauna diversity on agricultural land in Baturiti District and to determine the relationship between soil organic matter levels and soil macrofauna diversity on agricultural land in Baturiti District. Sampling locations were taken on two types of land use, two organic land cultivation systems at an altitude of 903-1259 meters above sea level and conventional land at an altitude of 925-1173 meters above sea level. The method in this study is the sampling method, taking soil macrofauna and soil organic matter by direct observation to the research location at the sampling point, namely 5 types of organic agricultural plants and 5 types of conventional agricultural plants which are considered representative of the presence of soil macrofauna and represent each type of plant in the study area. Soil macrofauna sampling was carried out using 2 methods, namely pit fall trap, quadratic method and hand sorting. Sampling of organic matter was carried out by hand sorting method, on organic and conventional land in Baturiti District. Soil macrofauna found in organic and conventional land were identified and calculated values: Diversity index (H'), Abundance index (R1), Dominance (C). Soil from organic and conventional land was analyzed for organic matter content (C). The data obtained were analyzed by hypothesis testing (t) using the SPSS application to determine the relationship between soil organic matter content and soil macrofauna. The results of this study indicate that the level of soil macrofauna diversity on organic land with an altitude of 903-1259 mdpl is in the medium category (1.493- 2.421) and the level of soil macrofauna diversity on conventional land with an altitude of 962- 1318 mdpl is in the medium category (1.011- 1,961). On organic land with an altitude of 903- 1259 mdpl and conventional land with an altitude of 962 mdpl and 1173 mdpl, there is no relationship between soil organic matter content and macrofauna diversity. Based on the results of the hypothesis test, it was shown that it was rejected. On conventional land with an altitude of 1318 meters above sea level, there is a relationship between soil organic matter content and macrofauna diversity. Based on the results of the hypothesis test, it shows that it is accepted.